2013
DOI: 10.1260/1756-8277.5.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pool Fire in a Large Enclosure with Water Mist

Abstract: This paper reports the results of an experimental study of suppression of pool fires in enclosed spaces using water mist. The main objective of the present study is to understand the mechanisms responsible for the suppression of pool fires using water mists. Experiments were conducted in a large compartment with n-heptane pool fires of different heat release rates. The temperature variations in the compartment were measured using K-type thermocouples fixed at two locations. A multi gas analyzer was used to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…But by decreasing the gas to liquid flow rate ratio, the droplets break up at a slower rate. As a result, a series of relatively large droplets are produced that do not follow the air flow like tiny droplets, [31,[43][44][45][46] and this leads to an increase in the size of chitosan nanoparticles and their PDI value.…”
Section: Effect Of Gas To Liquid Flow Rate Ratio On the Z-average Par...mentioning
confidence: 99%
“…But by decreasing the gas to liquid flow rate ratio, the droplets break up at a slower rate. As a result, a series of relatively large droplets are produced that do not follow the air flow like tiny droplets, [31,[43][44][45][46] and this leads to an increase in the size of chitosan nanoparticles and their PDI value.…”
Section: Effect Of Gas To Liquid Flow Rate Ratio On the Z-average Par...mentioning
confidence: 99%
“…The functions of water mist include fire extinguishing, cooling and attenuating thermal radiation [5][6][7][8]. Fire extinguishing effect is mainly through the fire source of the cooling and suffocation effect to achieve.…”
Section: Water Mist Rolementioning
confidence: 99%
“…Furthermore, Liu et al [25] reported that the enhancement of fire-extinguishing performance is due to the increased depletion and dilution rate of oxygen and the recurrent dynamic mixing. Lal et al [26] conducted n-heptane pool fire suppression of water mist at different heat release rates (HRRs) in a large enclosure. They reported that the fire suppression of water mist was attributed to the evaporation cooling of fine water droplets and the oxygen displacement by water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of atomizing gas type during discharge of the water mist is potentially dependent on the discharged flow direction relative to the fire source position. However, based on previous studies on twin-fluid atomizers [24][25][26][27][28][29], there are limited studies that perform experiments to examine the effects of the discharge area and atomizing gas type of the twin-fluid atomizer which can significantly affect the fire-extinguishing performance. Hence, investigations should be intensively conducted to better understand the detailed fire suppression mechanism of water mist and improve further the performance of water mist fire suppression systems via adoption of twin-fluid atomizers.…”
Section: Introductionmentioning
confidence: 99%